With a postponed success, Amir Ashraf rose to the title of Entrepreneur - Rozaimi, Abu Samah (2019)
As the saying goes, “Where there’s a will, there’s a way”. It is a fitting analogy to the Managing Director of Profix Engineering Sdn. Bhd., Amir Ashraf Hamzah, 35, who continued to struggle in the business and managed to position himself in line with successful entrepreneurs.